Metaverse in Education: Exploring the Potential of Learning in Virtual Worlds - Sitti Hartina; Muhammad Nurcholis; A. Erni Ratna Dewi (Journal of Pedagogi, 2024)
The digital age is bringing significant changes to education, with the metaverse as a technological innovation that offers great potential to revolutionize learning methods. Metaverse creates interactive learning experiences through 3D simulations and avatars, allowing students to learn in a virtual world that mimics real-world scenarios. This transformation changes the approach to learning to be more active, collaborative, and personalized, but also presents challenges, especially regarding accessibility and the digital divide. Students in rural areas often face constraints in accessing adequate devices and internet connections, while the cost of devices such as VR headsets remains high. In addition, issues of data security and privacy are important concerns, as students' personal data must be protected to strict standards. Metaverse also offers the opportunity to create an inclusive learning environment for people with disabilities, with features that can be customized to support their specific needs. However, maximizing the potential of the metaverse requires a paradigm shift in the curriculum, intensive training for teachers, and collaboration between the government, private sector and educational institutions. This research uses a descriptive qualitative approach to explore the potential and challenges of metaverse implementation in education, by collecting data through interviews, questionnaires and observations. The results show great benefits for learning, although access and data security challenges need to be addressed.